Corticomedullary differentiation of the kidney: Evaluation with noncontrast‐enhanced steady‐state free precession (SSFP) MRI with time‐spatial labeling inversion pulse (time‐SLIP). Issue 5 (13th November 2012) - Kanki, Akihiko; Ito, Katsuyoshi; Tamada, Tsutomu; Noda, Yasufumi; Yamamoto, Akira; Tanimoto, Daigo; Sato, Tomohiro; Higaki, Atsushi
Abstract Purpose: To assess whether noncontrast‐enhanced steady‐state free precession (SSFP) magnetic resonance imaging (MRI) with time‐spatial labeling inversion pulse (Time‐SLIP) can improve the visibility of corticomedullary differentiation of the normal kidney. Materials and Methods: A series of noncontrast‐enhanced SSFP MRI with Time‐SLIP were performed in 20 patients by using various inversion times (TIs); 500–1800 msec in increments of 100 msec. In‐phase (IP) and opposed‐phase (OP) MR images were also obtained. The signal intensity (SI) of the renal cortex and medulla was measured to calculate corticomedullary contrast ratio (SI of cortex/medulla). Additionally, the visibility of corticomedullary differentiation was visually categorized using a four‐point scale. Results: In SSFP with Time‐SLIP, corticomedullary contrast ratio was highest with TI of 1200 msec in eight subjects (40%), followed by 1100 msec in seven (35%) and 1000 msec in three (15%). The corticomedullary contrast ratio in SSFP with optimal Time‐SLIP (4.93 ± 1.25) was significantly higher (P < 0.001) than those of IP (1.46 ± 0.12) and OP (1.43 ± 0.14). The visibility of corticomedullary differentiation was significantly better (P < 0.001) in SSFP images with Time‐SLIP (averaged grade = 4.0) than in IP images (averaged grade = 2.63) and OP images (averaged grade = 2.05). Conclusion: SSFP MRI with Time‐SLIP can improve the visibility of renal corticomedullary differentiation without using contrast agents. J. Magn. Reson. Imaging 2012;37:1178–1181. © 2012 Wiley Periodicals, Inc.